The Otolaryngology boot camp: a scoping review evaluating commonalities and appraisal for curriculum design and delivery - Adom Bondzi-Simpson; C. J. Lindo; Monica Hoy; Justin T. Lui (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Surgical boot camps are becoming increasingly popular in Otolaryngology–Head and Neck Surgery (OHNS) residency programs. Despite pioneering virtual reality and simulation-based surgical education, these boot camps have lacked critical appraisal. The objective of this article was to examine the adoption and utility of surgical boot camps in OHNS residency training programs around the world. Data Sources Ovid Medline and PubMed databases were systematically searched in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for scoping reviews. Additionally, a grey literature search was performed. Review Methods Inclusion criteria were peer-reviewed publications and grey literature sources that reported on OHNS boot camps for the novice learner. The search was restricted to human studies published in English. Studies were excluded if they were not examining junior trainees. Results A total of 551 articles were identified. Following removal of duplicates, screening, and full text review, 16 articles were included for analysis. Seven major boot camps were identified across various academic sites in the world. Most boot camps were one-day intensive camps incorporating a mixture of didactic, skill specific, and simulation sessions using an array of task trainers and high-fidelity simulators focusing on OHNS emergencies. Studies measuring trainee outcomes demonstrated improvement in trainee confidence, immediate knowledge, and skill acquisition. Conclusion Surgical boot camps appear to be an effective tool for short term knowledge and skill acquisition. Further studies should examine retention of skill and maintenance of confidence over longer intervals, as little is known about these lasting effects.